EFISIENSI PRAKTIKUM FISIKA MELALUI PENYAJIAN LAPORAN HASIL PRAKTIKUM BERBASIS VIDEO PROJEK DALAM MENUMBUHKAN KEMAMPUAN SELF-LEARNING MAHASISWA - riswanto, riswanto; Alarifin, Dedy Hidayatullah; suseno, Nyoto; Harjati, Purwiro; Putra, Dian hartanto Setya (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Writing dozens of reports every semester in physics practicum is often a heavy burden for students, so a more efficient and innovative reporting method is needed to ease their tasks without reducing the quality of learning. This study analyzes the use of video in reporting physics practicum results to ease the burden on students in writing reports. Through videos, students can present information, explain concepts, and demonstrate the application of physics theories in a dynamic and interactive manner. Videos are expected to improve the quality of practicum reports, provide constructive feedback, and promote UM Metro's physics education program. This study used quantitative and descriptive qualitative methods with purposive sampling, involving 6th semester Physics Education students who took astronomy courses. Data were obtained from practicum video assessment rubrics, student response questionnaires, and in-depth interviews, analyzed through a 1-5 Likert scale. This study found that the Project-Based Learning model with video as a practicum report was effective in improving the self-learning of Physics Education students. The title of the video (97.27%) was most attractive, but improvement was needed in time management (55.00%) and simulation of results (67.27%).